The Significance of Teaching Academic English for English Language Learners - Andriansyah Andriansyah; Ayyub Abdurrahman; Regina Rahmi (IJELR: International Journal of Education, Language, and Religion, 2019)
In this paper, we will discuss some topics related to supporting English Language Learners (ELLs) in developing their English as an academic language. Firstly, we describe the general issues of ELLs; including what languages are learned the most. Secondly, we provide some topics related to the effectiveness of instructional practice in ELs’ teaching, type of instructional practices to support ELLs including some topics related to using L1 and L2 in teaching, the importance of teaching English at the younger aged or Teaching English to Young Learners. Lastly, we draw upon some issues related to the effective practice of teaching and learning for ELLs especially the importance of academic language, in particular to the English language learners. In addition, in this paper we use the term of ELLs and ELs, refers to the English Learners since the English Language Learners has been changing to be just English Learners (ELs) recently.